Paracrine Regulation of Steroidogenesis in Theca Cells by Granulosa Cells Derived from Mouse Preantral Follicles. (19th August 2015) - Liu, Xiaoqiang; Qiao, Pengyun; Jiang, Aifang; Jiang, Junyi; Han, Haiyan; Wang, Li; Ren, Chune
Abstract : Interaction partners of follicular cells play a significant role in steroidogenesis, follicular formation, and development. Androgen secreted by theca cells (TCs) can initiate follicle development and ovulation and provide precursor materials for estrogen synthesis. Therefore, studies on ovarian microenvironment will not only lead to better understanding of the steroidogenesis but also have clinical significance for ovarian endocrine abnormalities such as hyperandrogenism in polycystic ovary syndrome (PCOS). This study applied the Transwell coculture model to investigate if the interaction between granulosa and theca cells may affect androgen production in theca cells. Concentrations of testosterone and androstenedione in the spent medium were measured by radioimmunoassay and enzyme linked immunosorbent assay, respectively. The results show that the coculture with granulosa cells (GCs) increases steroidogenesis in TCs. In addition, testosterone and androstenedione productions in response to LH stimulation were also increased in the coculture model. Significantly increased mRNA expressions of steroidogenic enzymes ( Star, Cyp11a1, Cyp17a1, and Hsd3b2 ) were observed in the cocultured TCs. Thus, GCs were capable of promoting steroidogenesis and LH responsiveness in TCs. This study provided a basis for further exploration of ovarian endocrine mechanism and pathologies.